KUALITAS PELAYANAN ADMINISTRATIF PUBLIK DI KELURAHAN SEPINGGAN RAYA KOTA BALIKPAPAN - Marlindawaty Linda (Jurnal GeoEkonomi, 2020)
The goal to be achieved through this research is to find out and analyze how far the impact of the transfer of some tasks from Kelurahan Sepinggan Raya to The Department of Population and Civil Registration (DISDUKCAPIL) on the quality of services provided which results in satisfaction or not community members of the services provided by The Kelurahan Sepinggan Raya. The type of this research is quantitative descriptive with the method of data analysis techniques frequency table and Likert scale 4 points. Data collection was carried out through the distribution of questionnaires to 97 respondents. The results showed that in general the quality of public administrative services in Kelurahan Sepinggan Raya Balikpapan using the theory proposed by Payne regarding human resources, service processes and facilities and infrastructure was better but not yet optimal.